Análisis del desempeño de redes definidas por software frente a redes virtualizadas. estudio de caso - Moreira Villafuerte , Stiven Yiovanny (2023)
This study focuses on the analysis of the performance of software-defined networks versus virtualized networks, an area in the context where we denote that based on the high requests by users these architectures tend to be analyzed. Software-defined networks (SDN) based on how technology advances, are evolving in factors such as latency and jitter in the management of network traffic. Network functions virtualization (NFV) has a very promising approach for resource optimization but not for network traffic management. The research is based on the collection of data through practical scenarios in a virtual environment and the analysis of existing literature. The importance of understanding these two architectures, understanding which one adapts in terms of latency and jitter, leads us to better decision making to be able to respond to the high demands of users.